Characteristics of Old Women with Urinary Incontinence in a Rural Area - BANDO, Akiyoshi; TADA, Toshiko (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 1999)
We conducted a questionnaire survey of the state of health and daily living of the people over 65 years of age who live in a commercial district and an adjoining rural area. In this survey, subjects were asked to select answers to multiple-choice questions by themselves. The survey revealed various facts. Among them, our attention was riveted on the fact that loss of bladder control is a serious problem for many of the people of advanced age, especially women. So, we worked toward gaining an insight into the lifestyle of the aged with urinary incontinence. In both commercial and agricultural communities, predominantly more women than men complained of incontinence. Over 50% of them replied that the frequency of incontinence is once every day, more or less. There also were indications that the inability to control urination indubitably threatens the physical and mental well-being of the old people irrespective of sex. However, as far as women are concerned, problems associated with incontinence are more serious for inhabitants in the farming area than in the commercial district. Our analysis also found notable declines in ADL (activities of daily living) and physical functions among incontinent women in the farming area. We deem it important to reach out a helping hand to them.